Factors Associated with Pulmonary Function Disorders Among Workers in the Printing Area of PT X - Rizqiana Fauziyyah; Suhartono Suhartono; Nurjazuli Nurjazuli (Journal of Social Research, 2025)
Lung function disorders are among the occupational health problems frequently experienced by workers in industries exposed to chemicals, dust, and vapors generated during production processes. The printing area represents a work environment with a high potential for exposure to chemicals such as organic solvents (toluene, xylene, and formaldehyde), fine particulates, and combustion gases. The purpose of this study, Factors Associated with Pulmonary Function Disorders Among Workers in the Printing Area of PT X, is to identify and analyze factors related to impaired lung function among workers in the printing area based on a literature review. The method used is a systematic literature review involving article searches in the PubMed, ScienceDirect, ProQuest, and Google Scholar databases from 2013 to 2023. The synthesis results showed that work duration, exposure period, smoking habits, use of personal protective equipment, workspace ventilation, and concentrations of airborne chemicals were significantly associated with decreased pulmonary vital capacity (FVC) and first-second forced expiratory volume (FEV?). Continuous risk management efforts, including routine spirometry examinations, worker education, and ventilation engineering, are essential to reduce the risk of lung disorders in the printing industry.